Interaction with Nitric Oxide of the Nitrosomonas Europaea Tetraheme Protein Cytochrome C554, and Two of Its Variants, in Increasingly Reducing Environments - (:unkn) unknown (My University, 2017)
A re-investigation of the interaction with NO of the small tetraheme protein cytochrome c554 (C554) from Nitrosomonas europaea has shown that the 5-coordinate heme II of the 2-electron or 4-electron reduced protein will nitrosylate reversibly. The nitrosylation process was found to be first order in C554, first-order in NO, and second-order overall. The rate constant for NO binding to the heme was determined to be 3000 ± 140 M-1s-1, while the rate constant for dissociation was 0.034 ± 0.009 s-1; the degree of protein reduction does not appear to significantly influence the nitrosylation rate. In contrast to a previous report, [ Upadhyay, A. K., et al. (2006), J. Am. Chem. Soc. 128, 4330-4337] this study turned up no evidence of C554-catalyzed NO reduction, either with C55422- or with C55442-. Some sub-stoichiometric oxidation of the lowest potential heme IV was detected when C55444- was exposed to an excess of NO, and this could in principle be part of a process that yields N2O, though alternative explanations are equally plausible. The vacant heme II site of C554 is sterically crowded by three non-bonding hydrophobic amino acids, Thr 154, Pro 155 and Phe 156. Replacing Phe156 with a protonatable but still bulky histidine residue did not significantly alter the reactivity of the F156H mutant with NO, though the NO binding rate appeared to increase 10-fold. On the other hand, when Phe156 was replaced with the smaller but still hydrophobic alanine, the 6-coordinate low-spin hemes of the 4-electron reduced mutant oxidized over the course of several minutes after exposure to NO. Two-electron reduced F156A2 nitrosylated, but did not oxidize, upon exposure to NO. Notably, the nitrosylation rate for F156A2-and F156A4- was about 400x faster than for the wild type or for the F156H mutant, though the rate of the reverse denitrosylation process was almost the same for the three C554 variants. The midpoint potentials of C554, and of the F156A and F156H variants, were determined for all the hemes in these tetraheme proteins, using spectropotentiometric analysis. The heme II midpoint potential of F156H was profoundly altered from the wild type value, shifting about 170 mV to the negative. This is taken as evidence that the histidine ligand in the variant binds to the erstwhile vacant ferric heme II axial site, thus stabilizing the oxidized state. Consistent with this interpretation, the UV/Visible spectrum of fully oxidized F156H exhibited increased absorbance at 409 nm relative to the wild type, which suggests that the mutant protein has 4 low-spin ferrihemes, rather than three low-spin and one high-spin as seen in the wild type. Upon reduction of heme II though, the spectrum of F156H exhibited a band at 430 nm characteristic of high-spin ferrohemes, which suggests that His156 dissociates from the heme when this reduces. In contrast to the case with F156H, the midpoint potentials of hemes I and II in F156A were only slightly shifted relative to the wild type. On the other hand, the midpoint potentials of the low-potential hemes III and IV were shifted about 100 mV to the negative by mutating Phe156 to Ala, whereas mutation of Phe156 to His had minimal impact on these hemes. It appears that the substitution of bulky Phe by the small Ala significantly alters the conformation of the protein backbone, which in turn affects the environment of distant hemes enough to substantially alter their midpoint potentials. The lower heme III and IV midpoint potentials of F156A, together with the increased solvent access to the heme II vacant site in this variant, may work together in changing its reactivity to bound NO. The more strongly reducing hemes could more readily reduce bound NO, while increased solvent access could now allow protonation to accompany reduction of the bound nitrogen moiety.
Keywords: Ammonia Oxidizing Bacteria; Cytochrome C554; Nitric Oxide; Nitric Oxide Reductase; Nitrogen Cycle